INDIA’S GROWING SECURITY ARCHITECTURE IN INDO PACIFIC: A CASE STUDY OF INDO- MAURITIUS CONVERGENCE - Subhash Kumar Baitha; Souvik Chatterjee (Indonesian Association for International Relations, 2022)
The rise of China across the Indian and the Pacific Ocean along with new threats radiating from the maritime domain further consolidates the necessity of maritime security. All the major powers such as India, Japan, the United States, Australia, etc. are giving attention to the Indo-Pacific to counter China’s assertiveness and to protect their maritime interests. Concerning India, the country has adopted three approaches to protect its maritime and geostrategic interests in the Indo-Pacific region. First to directly engage with the regional powers and forums such as ASEAN. Secondly collaborating with small and middle powers such as the Maldives and Sri Lanka, Mauritius, and Seychelles, etc. Finally, engaging in multilateral and multi-sectoral dialogue with global powers such as Australia, Japan, the United States under the ambit of the Quadrilateral Security Dialogue, commonly called the Quad. Using littoral powers India is in the process of actively extending its reach, interests, and focus to subvert Chinese assertiveness. So based on the stated problem the focus of this paper is to understand the changing trajectory of India’s Indo-Pacific policy with special reference to Mauritius.